Constraints on the Timing of Explosive Volcanism at Aso and Aira Calderas (Japan) Between 50 and 30 ka: New Insights From the Lake Suigetsu Sedimentary Record (SG14 Core). (3rd August 2020) - McLean, D.; Albert, P. G.; Suzuki, T.; Nakagawa, T.; Kimura, J.‐I.; Chang, Q.; Miyabuchi, Y.; Manning, C. J.; MacLeod, A.; Blockley, S. P. E.; Staff, R. A.; Yamada, K.; et al.
Abstract: Volcanoes in the East Asian/Pacific region have been the source of some of the largest magnitude eruptions during the Late Quaternary, and accurately evaluating their eruptive histories is essential for hazard assessments. To overcome difficulties in resolving and precisely dating eruptions in the near‐source realm, the high‐resolution (varved) sediments of Lake Suigetsu (central Honshu, Japan) were examined for the presence of non‐visible (cryptotephra) layers from 50 ka up until the 30 ka Aira‐Tanzawa (AT) caldera‐forming event of Aira volcano. Cryptotephra layers are four times more frequently preserved than visible markers in the Suigetsu sediments, meaning that this archive provides a unique and unprecedented record of eruptions that were dispersed over the densely populated regions of central Honshu. Major and trace element volcanic glass chemistry is used to fingerprint the ash layers and pinpoint their volcanic origin. Tephras are found throughout the investigated sediments, but the highest abundance of ash fall events are recorded between 39 and 30 ka, capturing a period of intense volcanism at calderas on Kyushu Island (Japan). The augmented Suigetsu tephrostratigraphy records at least seven eruptions from Aso caldera (southern Kyushu) that post‐date the widespread ACP‐4 Plinian eruption (ca. 50 ka) and four explosive events from Aira (central Kyushu) that occurred leading up to the catastrophic caldera‐forming AT eruption (ca. 30 ka). Key Points: Refined eruption stratigraphy for Japan (between 50 and 30 ka) through the identification of cryptotephra layers in the varved Lake Suigetsu sediment core Aso caldera was particularly active between 35 and 30 ka, producing at least 5 tephras that were dispersed >500 km from source A large eruption occurred from Aira 1.3 ka before the cataclysmic VEI 7 caldera‐forming AT eruption that blanketed Japan in ash